Ghost in the tamarind : a novel - Shankar, Subramanian, 1962- (University of Hawaiʻi Press, 2017)
Who can you love? What do you owe to love and what to the world at large?Such are the questions that drive the story of Ramu, a Brahmin man, and Ponni, a woman of the Dalit "untouchable" caste. Set against the backdrop of twentieth-century South India, the novel takes readers from the 1890s village where Ramu's grandmother grew up to the Emergency years of 1970s Madras. Against this sweeping canvas unfolds the drama of Ramu and Ponni's forbidden love, inescapably intertwined with the great struggle against caste oppression. Caught up in the entanglements of love and politics, the couple risks everything to fight for a better society. Will they succeed?Steeped in history, this memorable inter-caste love story shows ordinary people moved to uncommon courage in their desire to make a difference in a ruthless world